Perceived socially responsible-HRM on talent retention: The mediating effect of trust and motivation and the moderating effect of other-regarding value orientation - Rawshdeh, Zainab Ali; Makhbul, Zafir Khan Mohamed; Rawshdeh, Mustafa; Sinniah, Suguna (Frontiers in Psychology, 2023)
Introduction Studies have shown that there is a growing interest in corporate social responsibility (CSR) and talent management, and the identified links between their aspects. Thus, the current study examined the relationship between socially responsible human resource management (SRHRM)–identified as CSR strategies and practices directed at employees to underpin the effectiveness of CSR implementation–and talent retention. In addition, this study employed a mediation-moderation framework with employee attitude (motivation and trust) as a mediating variable and other-regarding value orientation (ORVO) as a moderating variable. Thus, the current study contributes to talent management and CSR current knowledge by analyzing the depth of the relationship by way of exploring the moderating and mediating process. It answers the “how” and “when” questions and explains the mechanism through which an organization can use its socially responsible HRM practices for retaining talented employees. Methods A total of 418 people from the Klang Valley area in Malaysia participated in the study. The hypotheses in the study were tested using PLS structural equation modeling. Results The results of the study showed that (a) perceived SRHRM was positively related to talent retention, (b) this relationship was partially mediated by the employee’s attitude (motivation and trust), and (c) ORVO did not moderate the relationship between perceived SRHRM and talent retention. Discussion Furthermore, the study findings provide concrete and actionable recommendations on how to formulate and implement appropriate SRHRM policies and practices as they are not only essential for the successful implementation of external CSR programs but also essential for retaining talented employees and for improving their motivation and organizational trust.